(untitled) (Research, Society and Development, 2020)
The present study aims to identify, through literature research, how the disabled person is perceived in relation to gender and sexuality issues. This is a descriptive bibliographic research with a qualitative approach, executed from February to April 2020 in the Scielo database using the following descriptors: disability, sexuality and gender, considering the period of the last two decades. This research was developed in three phases. Initially, the descriptor “disability” was used and 3927 articles were found. In phase two, both descriptors “disability and sexuality” were employed in the search, and 35 articles emerged. In the third phase, the three descriptors “disability, sexuality and gender” were used, finding nine articles. Next, analysis of the information collected was performed through thematic content analysis. Thematic groups were defined as: Gender and sexuality; Disability; Disability and the confluence with gender and sexuality. Based on data analysis, it was found there is a shortage of literature that combines the descriptors disability, sexuality and gender, verifying that sometimes there is denial of the sexuality of disabled people.